Empat Pilar Keuntungan Aplikasi Pendapatan Daerah: Memudahkan, Mensmimplifikasi, Mempercepat, dan Mengoptimalkan di Bapenda Provinsi Sumatera Barat - Elijha, Mila Nor; Delta Dea Ananta; Syamsir; Rahmatul Ilham; Zahir Fikri Rashief Azwar (Indo-MathEdu Intellectuals Journal, 2026)
This study aims to identify and analyze the main benefits of implementing the E-Regional Revenue (E-Pendapatan Daerah) application in managing regional revenue, particularly revenue derived from local taxes and retributions. The research problem arises from the persistence of manual, complex, and inefficient payment and reporting processes, which may hinder the optimization of regional revenue management. This study employs a descriptive qualitative approach using a case study method. The research subjects are regional revenue management institutions that have implemented the E-Regional Revenue application. The informants include system administrators, policy-making officials, and technical officers directly involved in the operation and utilization of the application. The selection of research subjects was conducted using purposive sampling, based on their direct involvement and relevance to the research objectives. Data collection techniques consisted of document analysis, in-depth interviews, and limited observation of the application-based revenue management process. Data analysis techniques were carried out using qualitative descriptive analysis, involving data reduction, data display, and conclusion drawing, supported by source triangulation to ensure data validity. The findings indicate that the implementation of the E-Regional Revenue application provides four major benefits. First, service convenience is achieved through online payment facilities that eliminate the need for taxpayers to visit service offices, thereby improving time and cost efficiency. Second, complex bureaucratic procedures are simplified through transaction automation. Third, the application accelerates the availability of reports and information systems in real time. Fourth, accurate and timely data supports optimized decision-making by leaders without reliance on manual reports. In conclusion, the E-Regional Revenue application functions not only as a technical payment tool but also as a strategic instrument that enhances operational efficiency and accountability in regional government financial management.